Conservation strategies of citrus germplasm: in vitro and in vivo - Carimi F.; De Pasquale F.; D'Onghia A.M. (Improvement of the citrus sector by the setting up of the common conservation strategies for the free exchange of healthy citrus genetic resources, 2001)
Conservation of citrus genetic resources needs an integrated in situ and ex situ approach. In view of preventing dissemination of diseases, it is necessary to resort to ex situ conservation for maintenance of clean material, whereas reinfection may be avoided by using in vivo and in vitro conservation. Following specific guidelines, the collection field fulfilling specific requirements or the insect-proof screenhouse can ensure in vivo conservation of a healthy gene pool as well as pomological traits. For several species, in vitro culture may play a major role as a conservation strategy or even be the only option available. Despite their several advantages, in vitro techniques still display considerable constraints such as genetic instability and length of tissue storage.